2012
DOI: 10.1002/ajh.23333
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and treatment outcome of primary systemic light‐chain amyloidosis in Korea: Results of multicenter analysis

Abstract: Primary systemic light-chain (AL) amyloidosis a disorder characterized by accumulation of monoclonal light chains as aggregated amyloid fibrils in tissues of multiple organs to cause organ dysfunction and death (Kyle and Gertz, Semin Hematol 1995;32:45-59; Merlini and Bellotti, N Engl J Med 2003;349:583-596). Although there are quite a number of data regarding clinical features and treatment outcomes of AL amyloidosis, most of them are from western countries except for a couple of reports from Japan (Kyle and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Indeed, the clinical features and treatment outcomes were mainly correlated with the type and extent of organ involvement rather than by the number of plasma cells in patients with AL amyloidosis [24, 25]. By comparison, a previous study with longitudinal whole genome sequencing of a high-risk myeloma patients demonstrated tumor heterogeneity at diagnosis and identified potential mutations contributing to myeloma development as well as transformation from myeloma to overt extramedullary disease [26].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the clinical features and treatment outcomes were mainly correlated with the type and extent of organ involvement rather than by the number of plasma cells in patients with AL amyloidosis [24, 25]. By comparison, a previous study with longitudinal whole genome sequencing of a high-risk myeloma patients demonstrated tumor heterogeneity at diagnosis and identified potential mutations contributing to myeloma development as well as transformation from myeloma to overt extramedullary disease [26].…”
Section: Discussionmentioning
confidence: 99%
“…An association between the number of involved organs and mortality has been shown in patients with cardiac amyloidosis (11) and in overall AL amyloidosis patients (14). In the present study, the number of organs with amyloid involvement was selected as an independent predictor of mortality in patients with AL amyloidosis (Table 3).…”
Section: Discussionmentioning
confidence: 80%
“…Left and right ventricular (RV) functions assessed by conventional and advanced echocardiography [e.g., tissue Doppler echocardiography (TDE) and speckle tracking echocardiography] and cardiac biomarkers, such as cardiac troponin and brain natriuretic peptide (BNP), have been shown to be strong predictors of mortality in patients with AL amyloidosis (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, the majority of previous studies have been conducted in Western countries (3)(4)(5)(6)(7)(8)(9)(10)(11), and the predictors of mortality in Asian patients with AL amyloidosis have not yet been characterized (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall prognosis of pAL is poor, mainly because amyloid deposits in important organs such as the heart, liver and kidneys, and ultimately lead to organ failure and death. (4). In the last 15 years, substantial progress has been made in understanding the biology of the amyloid plasma cell clones and the mechanisms of organ damage; yet there are no specific treatments can be used to treat amyloidosis.…”
Section: Introductionmentioning
confidence: 99%